Adherence to Recommended Risk Management among Unaffected Women with a BRCA Mutation. Issue 1 (6th June 2016) - Buchanan, Adam H.; Voils, Corrine I.; Schildkraut, Joellen M.; Fine, Catherine; Horick, Nora K.; Marcom, P. Kelly; Wiggins, Kristi; Skinner, Celette Sugg
Abstract: Identifying unaffected women with a BRCA mutation can have a significant individual and population health impact on morbidity and mortality if these women adhere to guidelines for managing cancer risk. But, little is known about whether such women are adherent to current guidelines. We conducted telephone surveys of 97 unaffected BRCA mutation carriers who had genetic counseling at least one year prior to the survey to assess adherence to current guidelines, factors associated with adherence, and common reasons for performing and not performing recommended risk management. More than half of participants reported being adherent with current risk management recommendations for breast cancer (69 %, n = 67), ovarian cancer (82 %, n = 74) and both cancers (66 %, n = 64). Older age (OR = 10.53, p = 0.001), white race (OR = 8.93, p = 0.019), higher breast cancer genetics knowledge (OR = 1.67, p = 0.030), higher cancer‐specific distress (OR = 1.07, p = 0.002) and higher physical functioning (OR = 1.09, p = 0.009) were significantly associated with adherence to recommended risk management for both cancers. Responses to open‐ended questions about reasons for performing and not performing risk management behaviors indicated that participants recognized the clinical utility of these behaviors. Younger individuals and those with lower physical functioning may require targeted interventions to improve adherence, perhaps in the setting of long‐term follow‐up at a multi‐disciplinary hereditary cancer clinic.